A study of interaction among supply chain variables in electronics appliance industry in India. (1st January 2014) - Kumar, Pravin; Shankar, Ravi; Yadav, Surendra S.
In this paper, some of the major supply chain practices in electronics industry in India have been analysed. The hypotheses related to supply chain practices were formulated based on an intensive literature review. These hypotheses were tested using the statistical analysis of the data collected through questionnaire survey. The data were collected from electronics sector. Stepwise regression analysis has been used to know the relationship between select dependent variables (such as on-time delivery of products and services, mutual trust among supply chain partners, global competition, logistics costs, etc.) and independent variables (such as cost, quality, product design, desire to access global markets, security, fluctuating exchange rate of money, etc.). Finally, research is concluded and scope for future research is recommended.